PERLINDUNGAN HUKUM TERHADAP PEMBERI PINJAMAN AKIBAT KECURANGAN YANG DILAKUKAN PENYELENGGARA FINANCIAL TECHNOLOGY P2P LENDING - Audri Sesmita, (2022)
Technological developments have an impact in various sectors. One of those affected is the financial sector which has given birth to innovations in financial services and new investment instruments that utilize information technology. Peer to peer lending is the result of financial institutions to serve parties who need funds. The growth of P2P lending financial services is getting faster which cannot be avoided from the emergence of problems. The method used in this research is a normative juridical approach with a statutory approach and a conceptual approach, by collecting data using secondary data from primary, secondary and tertiary legal materials through library research, after being collected it will be analyzed qualitatively. Once collected, it will be analyzed qualitatively. In the study, the researchers looked for answers to the main problems that have been formulated, namely: First, how is the legal protection for lenders due to fraud committed by P2P Lending Fintech business operators. And second, what is the form of dispute resolution in the implementation of the Fintech P2P Lending business for lenders. The study resulted in conclusions regarding preventive and repressive legal protection, especially for lenders as regulated in OJK Regulation No. 77/POJK.01/2016 concerning Implementation of Information Technology-Based Borrowing and Borrowing of Money and dispute resolution that can be carried out by litigation or non-litigation in fraud committed by P2P Lending Financial Technology Operators. Thus, the provider of peer to peer lending has a responsibility to the lender as a consumer.